Faktor-Faktor yang Mempengaruhi Ibu dalam Melaksanakan Imunisasi Dasar Lengkap pada Anak di Puskesmas Miroto Kota Semarang - Kristianto Adiwiharyanto; Henry Setiawan; Bagoes Widjanarko; Dwi Sutiningsih; Syamsulhuda Budi Musthofa (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
ABSTRACTBackground: Complete basic immunization coverage in Indonesia in the last five years has not reached the target set in the Ministry of Health's Strategic Plan. Public health center as the operator of immunization operations must be supported by the implementation of a good health management function. The purpose of this study was to analyze the influence of facilitating factors, enabling factors, reinforcing factors and factorsthat influence mothers in carrying out complete basic immunization for children in relation to UCI achievement at Miroto Public Health Center, Central Semarang District, Semarang City.Methods: This study is analitic observational research with cross-sectional study design. The population of this research is mothers who have a minimum age of 1 under five who reside at Miroto Health Center. The research sample was 50 mothers with simple random sampling technique. Processing and data analysis with quantitative methods with univariate and bivariate analysis using the Chi Square test. Results: The results showed that there was an effect of mother's education level, mother's level of knowledge about completeness of basic immunization for infants, mother's employment status, number of children, family support, and effect on completeness of immunization.Meanwhile, family income does not affect the completeness of immunization.Conclusion: The achievement of UCI in the Public health center area of the Miroto Health Center is only 62% so that the follow-up reaches the target set at 95%.Variables that affect mothers in carrying out complete immunization are mother's education level, mother's level of knowledge, mother's employment status, number of children, family support, and what does not affect is family income.